High genetic similarity of ciprofloxacin-resistant Campylobacter jejuni in central Europe - Kovač, Jasna; Čadež, Neža; Stessl, Beatrix; Stingl, Kerstin; Gruntar, Igor; Ocepek, Matjaž; Trkov, Marija; Wagner, Martin; Smole Možina, Sonja (Frontiers in Microbiology, 2015)
Campylobacteriosis is the leading zoonosis in the European Union with the majority of cases attributed to Campylobacter jejuni. Although the disease is usually self-limiting, some severe cases need to be treated with antibiotics, primarily macrolides and quinolones. However, the resistance to the latter is reaching alarming levels in most of the EU countries. To shed light on the expansion of antibiotic resistance in central Europe, we have investigated genetic similarity across 178 ciprofloxacin-resistant Campylobacter jejuni mostly isolates in Slovenia, Austria and Germany. We performed comparative genetic similarity analyses using allelic types of seven MLST housekeeping genes, and the single nucleotide polymorphisms of quinolone resistance determining region located within the DNA gyrase subunit A gene. This analysis revealed high genetic similarity of isolates from clonal complex ST-21 that carry gyrA allelic type 1 in all three of these central-European countries, suggesting these ciprofloxacin resistant isolates arise from a recent common ancestor.